Mem?rias liter?rias na lousa digital: tecendo novos rumos para o ensino-aprendizagem de leitura-escrita na escola p?blica - De Ara?jo, Andreia Machado Castiglioni (2018)
This thesis had objectives like to improve the reading and writing of Literary Memories, through the creation of educommunication materials, developed in activities sequenced in the Digital Board, in the teaching-learning process of Portuguese Language of 7th grade students of a municipal school in Feira de Santana (BA). The Digital board enables the insertion of didactic-pedagogical objects with historical and cultural themes and the interaction between the students. These materials were elaborated based on a didactic sequence, produced by the teacher-researcher, as proposed by Dolz, Noverraz and Schneuwly (2004), which brings the singularity and popular narratives as the theme of Feira de Santana. In addition, the materials created appear as a stimulus to the local cultural manifestation, their respective insertion in the school routine, the constancy of the rewriting and the prevalence of student protagonism. In order to guide this research, the studies of Ricoeur (2003) and Smolka (2000) regarding the conception of memory have as theoretical background, Hall (2003) and Kellner (2001) in the cultural and identity sphere; the socio-interactionism (IVIC AND COELHO, 2010; VIGOTSKY, 2007); the use of new technologies and Digital board with L?vy (1999) and Nakashima and Amaral (2009); the textual genre Literary Memories with Clara and Altenfelder (2008) and (re) writing with Fiad (1997) and Borges (2016). The methodology used was qualitative, through an intervention proposal (DAMIANI, 2012), in order to demonstrate the students' progress in the textual production of the Literary Memories genre, comparing the initial text with the final text. The intervention took place in the first academic quarter (2017), in weekly meetings. For the production of data, we record in logbook and analysis grid of written productions, in addition to a diagnostic questionnaire and subject scripts. The results of this study point out that the use of multimodal resources contributes, qualitatively, to the teaching-learning process, besides stimulating the student protagonist performance, bringing frequency as one of the variables to advance the knowledge of the subjects. Still, we realize that the diffusion of local history and culture drives discoveries outside the school space, bringing the student closer to his community